Noninferiority clinical trial comparing the bowel cleansing efficacy of sodium phosphate tablets (Quiklean ® ) with a polyethylene glycol/bisacodyl kit - Hung, Shih-Ya; Chen, Hung-Chang; Ke, Tao-Wei; Chen, Jiann-Hwa; Hsiao, Koung-Hung; Wang, Hwei-Ming; Chiang, Hua-Che; Chang, Sheng-Chi; Chen, Yi-Chang; Hsieh, Ming-Hao; Tsai, Yuan-Yao; Hsieh, Yo-Wen; et al. (World journal of gastroenterology : WJG, 2021)
Efficient bowel cleansing is essential for a successful colonoscopy, but the ideal cleansing agent, volume, and pharmaceutical dosage form have yet to be determined. Small-volume cleansers enhance patient compliance. To compare the bowel cleansing efficacy of 32-tablet sodium phosphate (Quiklean ) with 2-L polyethylene glycol (PEG)/bisacodyl (Klean-Prep/ Dulcolax ) under identical dietary recommendations. This multicenter, randomized, parallel-group, noninferiority clinical trial enrolled 472 outpatients, randomized 456 subjects, and scheduled 442 subjects to undergo colonoscopy (Quiklean = 222 and Klean-Prep/Dulcolax = 220). After bowel preparation, a colonoscopist performed the colonoscopy with video recorded for rating. The primary efficacy endpoint was the bowel cleansing quality using the Aronchick Scale. The secondary endpoints were the bowel cleansing efficacy of three colon segments, tolerability and acceptability, safety using the Ottawa bowel preparation scale, questionnaires by subjects, and monitoring of adverse events. Success rates (Excellent + Good) of the bowel cleansing quality by Aronchick Scale were 98.6% ( = 205) and 97.6% ( = 204) in the Quiklean and Klean-Prep/Dulcolax groups, respectively. Quiklean demonstrated noninferiority over Klean-Prep/Dulcolax in colon cleansing efficacy. Quicken showed better tolerability and acceptability in the overall experience (was rated as excellent; 24.0% 17.2%; = 0.0016) and the taste of the study preparation (was rated as excellent, 23.1% 13.4%; < 0.0001) than Klean-Prep/Dulcolax . Safety profiles did not differ between the two groups. Our data indicate that Quiklean is an adequate, well-tolerated bowel cleansing preparation compared with the standard comparator Klean-Prep/Dulcolax . Quiklean is sodium phosphate tablets available on Taiwan's market for bowel preparation; it potentially offers patients an alternative to standard large-volume bowel preparation regimens and may, therefore, increase positive attitudes toward colonoscopies and participation rates.